Tantalum-based diffusion barriers for copper metallization - Khin Maung Latt. (2008)
The technological trend of shrinking integrated circuits in order to increase the logic density and improve the chip performance requires substituting copper for aluminium as interconnects in the deep sub-quarter micron ultra large scale integration (ULSI) devices. This trend is also reinforced by the fact that copper offers lower electrical resistivity.